EVALUATION OF WATER QUALITY GUIDELINES FOR DIFFERENT SOIL SERIES - Abid, Muhammad; Anwar-ul-Hassan; Ghafoor, Abdul; Wajid, Rana Abdul (Journal of Research (Science), 2003)
A fixed rating or evaluation is not possible for all the soils when considering the quality of water for irrigation. The recommended approach is to evaluate the water for the specific conditions at the locality where it is to be used. The experiments were conducted to develop the irrigation water quality guidelines for Rasulpur, Bhalike and Bhalwal soil series. Twenty undisturbed soil columns (76 cm long and 30 cm in diameter) were collected in metallic cylinders for the Rasulpur (sandy loam), Bhalike (clay loam) and Bhalwal (silty clay loam) soil series. The same numbers of packed columns in similar cylinders were also prepared for each soil series. The columns were irrigated with 20 brackish waters having EC @ 0.65, 2.0, 4.0, 6.0,7.35 dS m-1, SAR 3.95, 9.65, 18.0, 26.35 and 32.04 (mmol L-1)1/2 and RSC 0.65, 2.0, 4.0, 6.0, 7.35 mmolc L-1. The application of these waters was run for the period of four and a half years. Results indicated that the safe level of ECiw was up to 1.0, 0.8 and 1.0 dS m-1, respectively for the undisturbed Rasulpur, Bhalike and Bhalwal soil series. The safe level of SARiw was up to 12.0; 8.0; 10.0 for the undisturbed Rasulpur, Bhalike and Bhalwal soils, respectively. Similarly, RSC up to 2.0, 1.25 and 2.0 mmolc L-1, respectively was calculated as the safe level for the Rasulpur, Bhalike and Bhalwal soil series. Use of water having values higher than the upper limits of ECiw, SARiw and RSC for the respective soils mentioned above would be hazardous and their use for irrigation will require some additional management for sustainable use. It was also noted that undisturbed and disturbed soil conditions behaved almost similarly regarding the effect of ECiw, SARiw and RSC.